Multiplex detection of nine food-borne pathogens by mPCR and capillary electrophoresis after using a universal pre-enrichment medium - Villamizar-Rodríguez, Germán; Fernández, Javier; Marín, Laura; Muñiz, Juan; González, Isabel; Lombó, Felipe (Frontiers in Microbiology, 2015)
Routine microbiological quality analyses in food samples require, in some cases, an initial incubation in pre-enrichment medium. This is necessary in order to assure that small amounts of pathogenic strains are going to be detected. In this work, a universal pre-enrichment medium has been developed for simultaneous growth of Bacillus cereus, Campylobacter jejuni, Clostridium perfringens, Cronobacter sakazakii, Escherichia coli, Enterobacteriaceae family (thirty eight species, twenty seven genera), Listeria monocytogenes, Staphylococcus aureus, Salmonella spp. (two species, thirteen strains). Growth confirmation for all these species was achieved in all cases, with excellent enrichments. This was confirmed by plating on the corresponding selective agar media for each bacterium. This GVUM universal pre-enrichment medium could be useful in food microbiological analyses, where different pathogenic bacteria must be detected after a pre-enrichment step. Following, a mPCR reaction for detection of all these pathogens was developed, after designing a set of nine oligonucleotide pairs from specific genetic targets on gDNA from each of these bacteria, covering all available strains already sequenced in GenBank for them. The detection limits have been 1 Genome Equivalent, with the exception of Fam. Enterobacteriaceae (5 GEs). We obtained amplification for all targets (from 70 to 251 bp, depending on the bacteria type), showing the capability of this method to detect the most important industrial and sanitary food-borne pathogens from a universal pre-enrichment medium. This method includes an initial pre-enrichment step (18 h), followed by a mPCR (2 h) and a capillary electrophoresis (30 min); avoiding the tedious and long lasting growing on solid media required in traditional analysis (1 to 4 days, depending on the specific pathogen and verification procedure). An external testing of this method was conducted in order to compare classical and mPCR methods. This evaluation was carried out on five types of food matrixes (meat, dairy products, prepared foods, canned fish and pastry products), which were artificially contaminated with each one of the microorganisms, demonstrating the equivalence between the two methods (coincidence percentages between both methods ranged from 78% to 92%).